Effectiveness of an educational intervention in improving healthcare workers' knowledge of early recognition, diagnosis and management of rheumatic fever and rheumatic heart disease in rural far-western Nepal: a pre/post-intervention study. Issue 4 (22nd April 2022) - Bhatt, Navin; Karki, Ashmita; Shrestha, Biplav; Singh, Amul; Rawal, Lal B; Sharma, Sanjib Kumar
Abstract : Objectives: Rheumatic fever (RF) and rheumatic heart disease (RHD) remain among the major heart problems among children in Nepal. Although these conditions are preventable and treatable, the lack of proper knowledge and resources to diagnose and manage these conditions in rural health centres is a key concern. This study assessed the impact of educational sessions to improve the knowledge of healthcare workers in the early recognition, diagnosis, and management of RF and RHD in rural far-western Nepal. Design, setting and participants: This study used a pretest and post-test interventional design and was conducted among 64 healthcare workers in two primary healthcare centres and a peripheral district-level hospital in Achham district in the far-western region of Nepal. A self-administered questionnaire was used before and after the educational sessions. Data were analysed using SPSS V.21. Results: The overall test scores increased from 10 (SD=2.4) pre-intervention to 13.8 (SD=1.9) post-intervention (p<0.001). Similarly, participant confidence (graded 1–5) in differentiating bacterial from viral sore throat rose from 3.6 (SD=1.08) pre-intervention to 3.98 (SD=1.09) post-intervention (p<0.05). Confidence in managing RF increased from 3.9 (SD=0.88) pre-intervention to 4.30 (SD=0.8) post-intervention (p<0.001). Conclusion: The findings suggest that the investigated educational sessions are promising with respect to improving the knowledge and confidence of healthcare workers in the early recognition, diagnosis, and management of RF and RHD at the primary healthcare level. Further studies with a larger sample size and conducted in different parts of the country are warranted to assess the effectiveness and impact of scaling up such educational interventions in Nepal.